1981
DOI: 10.1002/joc.3370010206
|View full text |Cite
|
Sign up to set email alerts
|

Annual rain‐water over India, its variability and impact on the economy

Abstract: The total volume of rain-water over India has been computed for each of the years during the period 1871-1978 on the basis of the rainfall data for a fixed network of 306 raingauges. The mean, the standard deviation and the coefficient of variation of the series of annual rain-water volume are 3143 km3, 300 km3 and 9.5 per cent, respectively. The series is homogeneous and random. The serial correlation is 0.013 which is too low to suggest any relationship between successive terms. Gaussian distribution gives a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 5 publications
0
40
0
Order By: Relevance
“…The Indian summer monsoon, which provides 75 to 90% of the total annual rainfall over most parts of India during the 4 months from June to September, is vital to India's agriculture (Parthasarathy et al, 1992). The Indian monsoon circulation influences more than 60% of the Earth's population (Webster et al, 1998) due to its large-scale impact on food production, power generation, drinking water supply and overall economy (Mooley et al, 1981;Mooley and Parthasarathy, 1983;Parthasarathy et al, 1988a).…”
Section: Introductionmentioning
confidence: 99%
“…The Indian summer monsoon, which provides 75 to 90% of the total annual rainfall over most parts of India during the 4 months from June to September, is vital to India's agriculture (Parthasarathy et al, 1992). The Indian monsoon circulation influences more than 60% of the Earth's population (Webster et al, 1998) due to its large-scale impact on food production, power generation, drinking water supply and overall economy (Mooley et al, 1981;Mooley and Parthasarathy, 1983;Parthasarathy et al, 1988a).…”
Section: Introductionmentioning
confidence: 99%
“…2. The data for various periods were collected from different publications and Government sources, and the India Meteorological Department (Mooley et al 1981). The homogeneity or stationarity of the monthly data series was tested by the Swed and Eisenhart test and the Mann-Kendall rank test (WMO 1966), and it was found that, for all sub-divisions, the number of runs lies within the required limits of the 5% significance level (Parthasarathy et al 1987).…”
Section: Data/methodologymentioning
confidence: 99%
“…The nature of the frequency distribution has also been tested using the chi-square statistic with 10 equalprobability class-intervals (Cochran 1952). Mooley and Parthasarathy (1984), Parthasarathy et al (1990Parthasarathy et al ( , 1992Parthasarathy et al ( , 1993Parthasarathy et al ( , 1994Parthasarathy et al ( , 1995, Pant and Rupakumar (1997) and Mooley et al (1981) provide more detailed discussion of the methodology adopted for assessing the quality, completeness and homogeneity of these data sets.…”
Section: Data/methodologymentioning
confidence: 99%
“…It brings approximately 80 % of the region's annual rainfall. The ISM plays a key role in Indian agriculture, and its anomaly often results in huge economic and societal consequences (Mooley et al 1981;Mooley and Parthasarathy 1982).…”
Section: Introductionmentioning
confidence: 99%